Does the copper intrauterine device affect serum cancer antigen 125 levels? - Karaca, M.; Kumru, S.; Dikmeli, N. (Imr Press, 2007)
Purpose: This study aimed to reveal the effect of the copper IUD, if any, on serum CA-125 levels in patients who use the device as a contraceptive. Methods: Blood samples were obtained two times from 20 healthy volunteers before and after IUD insertion, and sera were isolated. The sera, centrifuged at 2000 G and kept at -70 degrees C in a deep freezer until analyzed, were processed for CA-125 levels by the CA-125 kit using VIDAS PC analyzer (Biomerieux, France) and results were compared. Results: The CA-125 level of the serum obtained from the first blood samples was significantly higher than that of the second sample (24.63 +/- 25.40 mIU/ml and 14.44 +/- 10.08 mIU/ml, respectively) (p < 0.05). Conclusion: The results of this study indicate that the serum level of CA-125 may be lower in patients using copper IUDs which may be helpful in evaluation of ovarian masses in women in reproductive age.
Keywords: CA-125; copper IUD